Santrifüj Pompa Performansının Ve Hidrolik Kuvvetlerinin Belirlenmesi - Çakır, Eren (Fen Bilimleri Enstitüsü, 2013)
Artan dünya nüfusu, gelişen teknoloji sanayide rekabet ortamını gün geçtikçe artırmaktadır. Bunun yanı sıra taleplere hızlı cevap verilmesi ve süreklilik sağlanması öncelik kazanmaktadır. Bilhassa, ilaç-kimya, kağıt, petrokimya ve enerji sektörlerinde yüksek güvenilirlik bekleyen sistemlerin taleplerinin karşılanması büyük önem arz etmektedir. Pompalama sistemleri bu süreçlerin kalbi sayılabileceğinden dolayı çalışan pompaların sürekliliği esas teşkil etmektedir. Yapılan araştırmalara göre bu ve benzeri 7/24 çalışan proseslerde kullanılan pompalardan öncelikli beklenti süreklilik ve güvenilirlik olmuştur. Enerji maliyetlerinin ilk aşamada geri plana atıldığı bu proseslerde pompaların bakım sürelerinin uzun periyotlarla olması beklenmektedir. Bu tür işletmelerde sistemlerin sürekliliğini ve güvenilirliğini etkiyen temel parametreler: - Projelendirme - Uygun ekipman seçimi - Ekipmanların amacına uygun ve verimli kullanılması - İzlenebilirlik olarak belirtilebilir. Bu parametreler göz önüne alındığında sistemdeki dinamik bileşen olan pompalar en önemli ekipman olarak ön plana çıkmaktadır. Bu sebeple pompaların doğru seçiminin önemli olmasının yanı sıra pompanın istenen çalışma değerlerinde kullanılmasına da dikkat edilmelidir. Pompaların tasarım değerlerinin dışında kullanılması pompalar üzerinde olumsuz etkiler oluşturarak süreklilik ve güvenilirlik açısından işletmelerde istenmeyen sonuçlar doğurmaktadır. Bu kapsamda pompaya etkiyen hidrolik ve mekanik kaynaklı kuvvetlerin sebep olduğu bu olumsuz etkilerin doğru tespiti de bir o kadar önemlidir. Bu açıdan hidrolik ve mekanik kaynaklı kuvvetlerin doğru tespit edilmesi mil dayanımı, yataklama gibi mekanik tasarımlar için oldukça önemlidir. Bu çalışmada sadece hidrolik kaynaklı kuvvetler üzerinde durulmuştur. Pompalarda oluşan hidrolik kaynaklı kuvvetler eksenel ve radyal kuvvetler iki ayrı kategoride incelenmektedir. Eksenel ve radyal kuvvetlerin büyüklüğü ise pompanın çalışma debisine göre farklılıklar göstermektedir. Bu kuvvetlerin büyüklüğüne göre: - Mil çapı - Mil uzunluğu - Yataklama tasarımı yapılmaktadır. Bu sebeple kuvvetlerin doğru tespit edilmesi pompaların tasarım parametrelerinin dışında dahi çalıştırılması durumunda sistemin sürekliliğinin sağlanması açısından oldukça mühimdir. Hidrolik kuvvetler, literatürde bulunan birçok hesaplama yöntemi ile hesap edilmesine rağmen kullanılan yöntemlere göre farklı sonuçlar çıkabilmektedir. Tez kapsamında eksenel kuvvet için Yazıcı, Gülich, HI yöntemleri olmak üzere 3 farklı yöntemle, radyal kuvvet için Gülich ve HI yöntemleri ile kuvvet hesaplamaları yapılacaktır. Elde edilen sonuçlar ise HAD ile belirlenen sayısal sonuçlarla karşılaştırılacaktır. HAD sonuçlarının doğruluğunu kontrol etmek için pompa performans deneyleri ile HAD sonucu elde edilen performans grafikleri karşılaştırılacaktır. Farklı yöntemlerle yapılan hesaplamalar sonucunda eksenel yükler için HI yönteminin diğer yöntemlere göre çok emniyetli çıktığı ve analiz sonuçlarının ise hesaplamalar sonucunda ortaya çıkan karakteristik yapı ile uyuşmadığı gözlenmiştir. Radyal yüklerde ise analitik yollarla elde edilen hesaplarla analiz sonuçları arasında uyum olduğu belirlenmiştir.

Population growth, technological developments has increased the competition in the market consistently. Besides, quick response for demands and regarding sustainability comes to first place. Especially, chemistry, petro-chemical, pulp and paper processes and energy sectors are required to high reliability. For this reason, determinations the best result for the demands of these system place an important role. Continuity of running pumps is the main factor in the pumping application due to the fact that pumping application is the hard of the system. During the past several decades, environmental consciousness of the population has increased dramatically and mankind started to question his effects on the environment. In connection this issues, not just the society but also the customers started to question the environmental effects of the products they use. Increasingly every year, consumers demand low carbon foot print products, which lead manufacturers to produce items that does not harm the environment. Pumps are recorded to be the second most common machinery on earth after electric motors. Recently centrifugal pumps are being designed and produced in various sizes and constructional features. For instance, miniature sized Blood Pumps, giant axial flow pumps with impeller diameters exceeding 4 meters for Flood Control and boiler feed pumps in Power Plants of motor power above 65.000HP. This wide range of application brings challenging problems to cope with on different levels of criticality. It is obvious that the problem arising in the design phase has no direct link to the size of the pump but closely related to application itself. As a result, specific requirements based on application specific standards and additional end-user measures are quite common and define every single step through design, production, quality control, testing, site installation and even shipment of the pump. According to the researches the priorities in the 7/24 working pumps is stability, continuity and confidence. It is expected that duration of the maintenance has long period in the process where energy cost put into the background. The main factor in this type of system which affects the system reliability and sustainability are shown as below: - Project management - Selection of suitable equipment - Relevant of operation of the equipment effectively - Commissioning Taking these parameters into consideration the pumps which is the dynamic component of the system can be indicated as the main factor. For this reason the selection of the pump has not only affect the system reliability. But also it is worthy to note that running of the pump correctly is significant. Running of the pumps out of the design criteria has negative effect on the pumps. As a result of these unexpected negative effects sustainability and reliability of the system can also be influenced. Also the determination of the forces which has an effect on the pump like hydraulic and mechanical is also important. It is worth to take into account of shaft strength and bearing for this type of mechanical design. The main purpose of the study is to determine the hydraulic forces. The forces on the pump are based on two categories. First one is axial, and the other one is radial forces. Magnitude of axial and radial forces can differ on pump operating conditions. According to magnitude of these forces, many criteria can be determined as below: - Shaft diameter - Length of shaft - Bearing design - Limit of vibration When the pumps are running out of design criteria, if the forces which affect the rotor of the pump calculated correctly sustainability is not affected in a bad way. Hydraulic forces, however there are many different calculation system in the literature the results may differ from calculation to calculation. In this study we use three different types of calculation: - Yazıcı - Gülich - Hydraulic Institute Calculations for the axial forces and for the radial forces we use Gülich and HI. The results will be compared with the numbers which will be determined by Computational fluid dynamics. Also to test the results of computational fluid dynamics, the result of the pumps performance test and the performance graphics of computational fluid dynamics will be compared. We have used different calculation methods and as a result HI seems to be the most secure calculation method for axial forces. But the result of analyzes is not a match with characteristic structure we get from the calculation methods. In radial forces we observe that the analytic calculations are a match to analytic results.
Specify The Centrifugal Pump Performance And Hydraulic Loads
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: Santrifüj pompalar; sayısal hesaplama; sayısal akışkanlar dinamiği; hidrodinamik kuvvetler; Centrifugal pumps; numerical calculation; computational fluid dynamics; hydrodynamics forces